2019
DOI: 10.1016/j.bioelechem.2019.107333
|View full text |Cite
|
Sign up to set email alerts
|

Electro-fermentation and redox mediators enhance glucose conversion into butyric acid with mixed microbial cultures

Abstract: Electro-fermentation (EF) is an emerging and promising technology consisting in the use of a polarized electrode to control the spectrum of products deriving from anaerobic bioprocesses. Here, the effect of electrode polarization on the fermentation of glucose has been studied with two mixed microbial cultures, both in the absence and in the presence of exogenous redox mediators, to verify the viability of the proposed approach under a broader and previously unexplored range of operating conditions. In unmedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…While such an effect could in principle be related to a pH buffering effect caused by the conversion of protons to H 2 , this was in fact found to be relatively minor (see the pH pro les in Figure 6b). The enhancement of the fermentation reactions when coupling the biological process with an electrochemical system was also reported by Paiano et al (2019), who observed an increased amount of metabolic products when exogenous redox mediators were used.…”
Section: Bio-electrochemical Testssupporting
confidence: 60%
“…While such an effect could in principle be related to a pH buffering effect caused by the conversion of protons to H 2 , this was in fact found to be relatively minor (see the pH pro les in Figure 6b). The enhancement of the fermentation reactions when coupling the biological process with an electrochemical system was also reported by Paiano et al (2019), who observed an increased amount of metabolic products when exogenous redox mediators were used.…”
Section: Bio-electrochemical Testssupporting
confidence: 60%
“…The pH impacted not only the fermentation pathway but also the microbial community structure. 17 However, the addition of BC or NDBC to the bioH 2 evolution system exerted no obvious influence on the start-up phases, indicating that the anaerobes in all the bioreactors could adapt to the pH changes during the bioH 2 generation processes. This phenomenon further confirmed that either BC or NDBC affected the bacterial concentration and community structure or promoted electron transfer during bioH 2 evolution.…”
Section: Resultsmentioning
confidence: 96%
“…In addition, electrofermentation depends on the possibility of affecting metabolic pathways by either donating electrons to microbes or changing the oxidation reduction potential of the reaction medium. 17 Nevertheless, to the best of our knowledge, there are no studies on the application of NDBC in H 2 or CH 4 production processes through anaerobic fermentation. Moreover, there is also a lack of understanding of how BC species and features ultimately influence the microbial community and functionality, subsequent H 2 and CH 4 yields, and liquid products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 4, a lag phase of approximately 20 days was observed in terms of acetate production, with a consequent high production of hydrogen (Figure S3). Despite the possibility to convert COD in other VFA anions by an electrofermentation pathway [30], no other volatile fatty acids other than acetate have been detected in all the reported bioelectrochemical tests. The system entered a steady state condition at around the 20th day of operation, with an acetate concentration of 102 ± 14 mg/L in the cathodic chamber while, thanks to the migration of the acetate, the anodic acetate concentration reached 526 ± 95 mg/L, which resulted in a five times higher acetate concentration.…”
Section: Continuous Bioelechtrochemical Reactormentioning
confidence: 94%